EFFETS DU LIT ET DE LA DENSITÉ DE PLANTATION SUR LA CROISSANCE VÉGÉTATIVE DE L’ANANAS (ANANAS COMOSUS L., VAR. MD2) DANS LA LOCALITÉ DE DABOU EN CÔTE D’IVOIRE - Généfol, Ouattara; Lezin, Bomisso Edson; Mamadou, Cherif; Brahima, Camara; Fatogoma, Sorho; Emmanuel, Dick Acka; Daouda, Kone; Eugène, Yocoli (European Scientific Journal, ESJ, 2015)
The aim of this study was to identify the best planting bed and density for vegetative growth of Ananas comosus L. var. MD2 plants in the locality of Dabou in Côte d’Ivoire. The effects of three planting beds : flat land, ridge without polyethylene film and ridge covered with polyethylene film ; and two planting densities : 50,000 and 70,000 plants/ha (D50 and D70, respectively) were tested through a split-plot disposition. At the end of the vegetative phase of the cycle, growth parameters were evaluated. The results showed that D70, average heights apical bunches were higher (91.52 cm) than D50 (86.87 cm). The number of fresh leaves varied between 48 and 51. The ridge covered with polyethylene film was distinguished with a number of relatively larger fresh leaves. The follow-up of the D leaves biomass revealed that seven months, the value of 70 g required to trigger floral induction therapy (FIT) had been reached in all plants, whatever planting bed and density. The flat land - density 70,000 plants/ha combinaison was illustrated with the D leaves biomass the highest (80.20 g). The weight of the fruit beingrelated to the plant’s growth during the floral induction therapy, at the end of the vegetative phase, the results could contribute to improving the production of MD2 pineapple in locality of Dabou.